EXPLORING THE ROLE OF IMPLICATURE IN LANGUAGE AND COMMUNICATION - Yuldasheva Maftuna (University Research Base, 2024)
This article delves into the exploration of the concept of implicature, a crucial aspect of pragmatics within linguistic studies. It seeks to unpack the theoretical underpinnings and the practical ramifications of how meaning is implied, rather than directly stated, in communication. Implicature serves as a sophisticated mechanism allowing individuals to express ideas and intentions beyond the mere literal words spoken. The discussion extends to the origins of the term, introduced by H. P. Grice in 1975, who identified the indirect conveyance of meanings as a fundamental component of effective communication. Grice highlighted the importance of adhering to conversational maxims, such as ensuring relevance to the conversational context, to facilitate this indirect communication. Furthermore, the article distinguishes between two forms of implicature: conventional and conversational. Conventional implicature is associated with the inherent meaning of specific linguistic expressions, while conversational implicature emerges from the situational context of the dialogue. This nuanced use of language enables speakers to subtly convey messages without explicit articulation, varying significantly across different cultures and linguistic traditions. The article underscores the applicability of implicature beyond linguistics, touching upon its significance in philosophy and psychology, particularly in understanding cognitive processes and social interactions. Through various examples and analyses, the article illustrates the pervasive role of implicature in everyday communication, highlighting its importance in the broader study of language and human interaction.